The Role of Emotions in Austrian Neutrality and Current Austrian Foreign Policy - Hauthaler, Lisa; Rolenc, Jan Martin, 1980-; Zemanová, Michaela; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The present Maters thesis explores the emotional association of Austrian citizens with the country's policy of neutrality. This study employs a constructivist approach and uses a critical discourse analysis of nine interviews with a non-probability sample to explore emotions. The results suggest that emotions such as disappointment, shame, gratitude, security, nostalgia, and pride are commonly associated with neutrality in Austria. The implications of these emotions on current Austrian foreign policy are discussed, with the study finding that emotions are likely to impact the process and outcome of decision-making in foreign policy. This study contributes to the existing literature on constructivism, neutrality, and emotions in international relations and provides a different perspective on understanding Austrian neutrality.
Vedoucí práce: Jan Martin Rolenc
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses